The Dominating Role of Genetic Background in Shaping Gut Microbiota of Honeybee Queen Over Environmental Factors - Yang, Jiandong; Zhong, Yun; Xu, Liqun; Zeng, Bo; Lai, Kang; Yang, Mingxian; Li, Diyan; Zhao, Ye; Zhang, Mingwang; Li, Debing (Frontiers in Microbiology, 2021)
A balanced, diverse gut microbiota is vital for animal health. The microbial population is shaped by multiple factors including genetic background and environment, but other determinants remain controversial. Numerous studies suggest the dominant factor is genetic background while others emphasize the environmental factors. Here, we bred asexual hybridization queens (AHQs) of honeybees through nutritional crossbreeding (laid in Apis mellifera colony but bred in Apis cerana colony), sequenced their gut microbiome and compared it with normally bred sister queens to determine the primary factor shaping the gut microbiota. Our results showed that the dominant genera in the gut microbiota of AHQs were Brevundimonas, Bombella and Lactobacillus, and its microbial community was more related to A. mellifera queens. The AHQs had a moderate number of different bacterial species and diversity, but total bacterial numbers were low. There were more significant taxa identified in the comparing between AHQ and A. cerana queen according to LEfSe analyses results. The only genetic-specific taxon we figured out was Brevundimonas. The growth of core bacterial abundance showed different characteristics among different queen groups in the first week after emerging. Collectively, this study suggested that the genetic background played a more dominant role than environmental factors in shaping the gut microbiota of honeybee queen and the microbiota of midgut was more sensitive than that of rectum to this impact.